Epidemiology and Drug Resistance of Neonatal Bloodstream Infection Pathogens in East China Children’s Medical Center From 2016 to 2020 - Zhang, Xin; Li, Yang; Tao, Yunzhen; Ding, Yu; Shao, Xuejun; Li, Wei (Frontiers in Microbiology, 2022)
Introduction To analyse the pathogen distribution and drug resistance of newborns with bloodstream infection (BSI) to help clinicians choose the appropriate empirical antibiotic therapy for clinical infection control. Methods A total of 707 neonatal BSI cases were retrospectively analysed. The bacteria in blood culture-positive samples were cultured, identified and analysed for drug sensitivity by routine methods. Statistical software was used to compare and analyse the basic data, pathogenic information, and drug resistance of the main bacteria. Results The five-year average positive rate of neonatal blood culture was 2.50%. The number of specimens submitted for inspection in 2020 significantly decreased. The top five infectious pathogens with the highest proportion were coagulase-negative Staphylococcus (67.35%), of which Staphylococcus epidermidis had the highest proportion (31.26%), followed by Escherichia coli (12.87%), Klebsiella pneumoniae (9.05%), Streptococcus agalactiae (8.63%) and Staphylococcus aureus (3.25%). G+ bacteria was dominant, accounting for 69.45%. The main G+ bacteria had a higher rate of resistance to erythromycin and penicillin G. The main G- bacteria had a high resistance rate to a variety of antibacterial drugs, especially cephalosporin antibiotics. The overall resistance of Klebsiella pneumoniae was higher than that of Escherichia coli. The top two fungi detected were Candida parapsilosis and Candida albicans. Candida parapsilosis did not appear to be resistant to antibiotics, while Candida albicans was resistant to multiple antibiotics. The type of microbial infection had a statistically significant difference in the positive rate among the age of delivery and wards (p < 0.05). There were significant differences in the detection of fungi among these groups (p < 0.05). The positive rate of G+ bacteria in the term newborns was significantly higher than that in the preterm newborns (p < 0.05). Preterm newborns are more susceptible to pneumonia. Conclusions G+ bacteria are the main pathogens of neonatal BSI. Preterm newborns are more likely to be infected with G- bacteria. Escherichia coli and Klebsiella pneumoniae are the most common G- bacteria, and both have a high resistance rate to a variety of antibacterial drugs. According to the distribution characteristics and drug resistance, it is very important to select antibiotics reasonably.